Agresividad y Pro-Sociabilidad: La Dinámica de Riesgo y Protección en los Procesos de Popularidad y Bullying - Lisboa, Carolina; de Oliveira Dias, Tatiane; Koller, Silvia Helena; DeSousa, Diogo (Psykhe, 2011)
Previous research has shown that positive psychological characteristics can moderate the relationship between aggression and developmental outcomes. This study assessed whether pro-sociability could moderate the association between aggression and victimization, and aggression and popularity. A convenience sample of 253 Brazilian children of low socioeconomic status (M age = 11.82, SD = 1.41) participated in the study. Structural equation modeling showed that the interaction between aggression and pro-social behaviors did not decrease children’s chances of being victimized and did not alter the association between aggression and popularity. Aggression seemed to be a predictor of bullying and pro-sociability, of popularity. These results contradict findings from previous studies that showed an association between aggression and positive behaviors such as pro-sociability. More studies are necessary to highlight cultural and contextual differences, comparing these results to those of other Latin American samples.